Моделювання пропозиційного фрейму «емоційний стан Heimweh» - Близнюк, Людмила Миколаївна; Blyznyuk, Lyudmyla (My University, 2015)
The status of Heimweh as a constituent part of propositional frame of emotional state situation is investigated. The aspects, according to which the status of Heimweh can be characterised, are identified. The markers that indicate the beginning, the end and the dynamics of the status of Heimweh are determined.